Beggar-thy-neighbor or beggar-thyself? The income effect of exchange rate fluctuations - Cédric Tille (Federal Reserve Bank of New York, 2000)
This paper analyzes the impact of exchange rate fluctuations when they are only partially passed through to consumer prices. We show that an exchange rate depreciation does not necessarily have a beggar-thy-neighbor effect and may in fact have an opposite, or beggar-thyself, effect. The direction of the welfare effect depends on who owns the firms importing goods from producers and selling them to consumers, an issue that has not been explored in the earlier literature.
Keywords: F31; F41; F42; 330; beggar-thy-neighbor; imports distribution; Wechselkurspolitik; Abwertung; Einkommenseffekt; Exchange Rate Pass-Through; Theorie